THE COMPLEXITY OF PUMPING WATER TO THE BOTTOM OF OIL WELLS - Rashidov Sanjar Uchkun ugli; Makhmatmuratov Farkhod Dilmurod ugli; Erdanov Bekhruz Sanjar ugli (Web of Journals Publishing, 2025)
The reduced pressure spreads along the perforation channels, and after a certain distance from the well, the influence of the perforation channels on the pressure distribution becomes negligible, and the flow takes a flat radial form in the direction of the well axis. We call the formation zone around the well up to this limit the active zone of the formation. Here, the flow has a very complex, localized structure near the perforation channels, the greatest pressure gradient and fluid flow velocity.
Keywords: Well, perforation works, various technologies, flow covers, technological operations, operational column